High-grade B-cell lymphoma: how to diagnose and treat. Issue 7 (3rd July 2019) - Novo, Mattia; Castellino, Alessia; Nicolosi, Maura; Santambrogio, Elisa; Vassallo, Francesco; Chiappella, Annalisa; Vitolo, Umberto
ABSTRACT: Introduction : High Grade B-cell Lymphomas (HGBL) have been defined as a new separate entity in 2016 revised WHO classification of lymphoid neoplasms. The previously well-known Double- and Triple-Hit Lymphomas (DHL/THL) are included in this umbrella category under the name of HGBL with MYC and BCL2 and/or BCL6 rearrangements (HGBL, R). A comprehensive diagnosis of HGBL is laborious, the diagnostic analyses required are expensive and time-consuming; moreover, a uniform consensus on which patients should be investigated has not been reached yet. Furthermore, there is no agreement on a standard therapeutic approach for this entity. Areas covered : In this article, the biological and clinical peculiarities of HGBL will be reviewed and all tools for a comprehensive diagnosis as well as the current therapeutic landscape will be investigated. Expert opinion : HGBL, R remains a challenging disease in terms of diagnosis and further research should be performed in order to define clear guidelines determining which cases have to be investigated thoroughly with FISH and other probes. Unsatisfying results have been shown in patients with HGBL, R treated with intensified chemoimmunotherapy strategies, therefore, larger prospective clinical trials should be conducted. Investigation into novel drugs that could lead to improvement of the current therapeutic approach should also be addressed.